(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Turmeric (Curcuma longa) has been a fundamental element of traditional medicine for ages, especially in Ayurvedic and Chinese practices. The bioactive molecule curcumin has attracted considerable interest for its medicinal potential. This review examines the therapeutic qualities of turmeric, emphasizing its anti-inflammatory, antioxidant, and antimicrobial actions. Turmeric's capacity to regulate many signaling pathways, including NF-kB, MAPK, and PI3K/Akt, enhances its therapeutic efficacy in the management of chronic conditions such as cancer, cardiovascular illnesses, and neurological disorders. Furthermore, turmeric's efficacy in wound healing, intestinal health, and metabolic regulation is examined. The review also examined the problems related to curcumin's bioavailability and methods to improve its medicinal efficacy. Turmeric's diverse medical characteristics render it a viable natural substance for both preventive and therapeutic applications. Additional research is necessary to thoroughly clarify its therapeutic potential and enhance its applications in contemporary medicine.